Pengembangan Media Interaktif Berbasis Problem Based Learning pada Materi Sistem Indra Manusia - Riza Nazila Azri; Miza Nina Adlini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop interactive learning media based on Problem Based Learning for the human sensory system topic that is valid, practical, and effective for students’ creative thinking skills. The method used was Research and Development with the 4D development model, consisting of Define, Design, Develop, and Disseminate stages. The results showed that the media obtained a validity level of 98.44% based on media expert assessment and 96.88% based on material expert assessment, teacher response of 95.83%, student response of 96.00%, and an N-Gain score of 0.83 in the high category. In conclusion, the interactive learning media based on Problem Based Learning is valid, practical, and effective, making it suitable for use in human sensory system learning to facilitate students’ creative thinking skills. Keywords: Creative Thinking Skills, Human Sensory System, Interactive Learning Media, Problem Based Learning.